2014
DOI: 10.1016/j.jss.2013.09.026
|View full text |Cite
|
Sign up to set email alerts
|

An intact parathyroid hormone–based protocol for the prevention and treatment of symptomatic hypocalcemia after thyroidectomy

Abstract: Background Symptomatic hypocalcemia after thyroidectomy is a barrier to same day surgery, and the cause of ER visits. A standard protocol of calcium and vitamin D supplementation, dependent on intact parathyroid hormone (iPTH) levels, can address this issue. How effective is it? When does it fail? Methods We performed a retrospective review of the prospective Thyroid Database from January 2006 to December 2010. 620 patients underwent completion (CT) or total thyroidectomy (TT), and followed our post-operativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 30 publications
(51 reference statements)
0
28
0
1
Order By: Relevance
“…These were managed according to established protocols. [3] Additionally, 23% of patients initiated or received a phone call to discuss results of laboratory tests or pathology while a similar number needed to discuss medications (changes in dosing, starting or stopping pills). Other reasons for postoperative calls are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…These were managed according to established protocols. [3] Additionally, 23% of patients initiated or received a phone call to discuss results of laboratory tests or pathology while a similar number needed to discuss medications (changes in dosing, starting or stopping pills). Other reasons for postoperative calls are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Predicting postoperative hypocalcemia using PTH has been extensively studied in recent years 8,[12][13][14]17,20 and various authors have attempted to ascertain the optimal time point at which to measure the PTH level. Noordzij et al 13 analyzed the pooled data from nine studies, finding that the PTH level 6 hours after surgery had the highest accuracy for predicting hypocalcemia.…”
Section: Discussionmentioning
confidence: 99%
“…11 Prior to 2008, most patients at our institution remained in hospital for at least 2 days postoperatively to monitor for hypocalcemia, and supplementation was initiated, if required. In recent years, multiple studies have demonstrated that a low postoperative PTH can predict hypocalcemia; [12][13][14][15][16] however, its accuracy may be as low as 80%. 17 The halflife of PTH is approximately 2 to 3 minutes; 18 therefore, specimens sent from the recovery room should predict postoperative parathyroid status.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the traditional markers of morbidity and mortality do not necessarily apply to thyroidectomy where the mortality rate approaches zero, but the morbidity can be significant (27)(28)(29)(30). The American College of Surgeons (ACS) developed a surgical risk calculator that can be used to estimate the risks of most operations and will allow clinicians and patients to make decisions using empirically derived, patient-specific postoperative risks (31).…”
Section: Discussionmentioning
confidence: 99%